NILAI KARAKTER TANGGUNG JAWAB DALAM BUKU CERITA ANAK KELUARGA CEMARA KARYA ARSWENDO ATMOWILOTO - Muhammad Arief Budiman; Ikha Listyarini (Jurnal CULTURE (Culture, Language, and Literature Review), 2022)
This study aims to analyze the value of the character of responsibility in the Cemara Family Children's Storybook by Arswendo Atmowiloto. This type of research is a qualitative research with descriptive method. The data in this study was carried out using the Cemara Family story book which contains character values. The sample was taken using purposive sampling, namely from thirty-nine subtitles, fifteen subtitles were taken from 3 sets of titles as samples. Based on the results of the analysis of research data through descriptions, it was found that the character values ​​in the Cemara Family children's story book by Arswendo Atmowiloto were found. The value of the character is shown through the sentences in each story. Of all the stories analyzed, there are 12 stories that show the value of the character of responsibility.